(untitled) (Third Sector Social Economic Review, 2017)
The sample of this study conducted to determine the Ecological Footprint Awareness levels of consumers is composed of 385 consumers residing in different districts of Ankara selected by stratified sampling and simple random sampling methods. The ""Ecological Footprint Awareness Scale"" was used as a data collection tool in the study. As a result of the study, consumers were found to have a low level of Ecological Footprint averages. The factor with the highest ecological footprint awareness level was found to be the food factor and the factor with the least awareness level was determined to be the energy factor. It was also found that men had more awareness of Ecological Footprint than women and showed a significant difference in waste factor according to educational status. In the future, researchers are suggested to work on the preparation of educational materials by using technology to improve consumer awareness of Ecological Footprint.